2012
DOI: 10.1002/j.1681-4835.2012.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption and Use of ICT in Thailand and Vietnam

Abstract: This exploratory study compares the adoption and use of ICT in the developing nations of Vietnam and Thailand by examining the nature and structure of the IT profession in medium to large size organizations. A theoretical framework is used with three related components: domains of IT professional expertise; the scope of the IT professional's knowledge, skills, and experience; and specific knowledge and skills associated with the domains of professional expertise. The findings provide insights that are not foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…The theoretical framework used in this study describes the knowledge and skills required of IT professionals using 3 components: 6 domains of IT professional expertise; items representing the expertise associated with each of the 6 domains; and sourcing strategies that organizations may adopt in order to acquire fundamental IT skills and knowledge. Earlier forms of this framework were used in 8 studies conducted in developing nations including exploratory studies of ICT in Vietnam (Lau et al, ; Winley & Lau, ) and Myanmar (Lau, Winley, Lau, & Tan, ) as well as studies of IT professional knowledge and skills, ICT education, and national ICT policies in Thailand (Winley, Arjpru, & Wongwuttiwat, ; Winley & Wongwuttiwat, ; Winley & Wongwuttiwat, ; Wongwuttiwat, ; Wongwuttiwat, Arjpru, & Winley, ). It is noted that the data for the 2 studies in Vietnam by Winley and Lau () and Lau et al () were collected in early 2011.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…The theoretical framework used in this study describes the knowledge and skills required of IT professionals using 3 components: 6 domains of IT professional expertise; items representing the expertise associated with each of the 6 domains; and sourcing strategies that organizations may adopt in order to acquire fundamental IT skills and knowledge. Earlier forms of this framework were used in 8 studies conducted in developing nations including exploratory studies of ICT in Vietnam (Lau et al, ; Winley & Lau, ) and Myanmar (Lau, Winley, Lau, & Tan, ) as well as studies of IT professional knowledge and skills, ICT education, and national ICT policies in Thailand (Winley, Arjpru, & Wongwuttiwat, ; Winley & Wongwuttiwat, ; Winley & Wongwuttiwat, ; Wongwuttiwat, ; Wongwuttiwat, Arjpru, & Winley, ). It is noted that the data for the 2 studies in Vietnam by Winley and Lau () and Lau et al () were collected in early 2011.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%
“…In the study conducted in Vietnam in 2011 by Winley and Lau (), it was found that 83% of organizations predicted that over the next 5 years there would be a significant increase in the demand for expertise in Domain 1 rather than the decrease shown in Table . However, for Domains 2, 3, and 4, the increases predicted by Morello () in Table were supported by approximately 68% of the Vietnamese organizations with no indication of any significant decreases in demand for these 3 domains.…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%
See 3 more Smart Citations